Frequency of Chemotherapy Induced Neutropenia in Patients of Non Hodgkin’s Lymphoma (Medical Forum Monthly, 2024)
Objective: The aim of the study is to see the frequency and severity of neutropenia after first or subsequent cycles of chemotherapy in patients of Non Hodgkin’s lymphoma (NHL).Study Design: Descriptive cross sectional study.Place and Duration of Study: This study was carried in the Radiotherpay & Oncology Department, Bolan Medical Complex Hospital, Quetta, from March 2010 to February 2012.Patients and Methods: Forty two patients of different types of NHL diagnosed on lymph node biopsy presenting for the first time at Radiotherapy & Oncology Department in collaboration with Haematology Section (Pathology Deptt:), Bolan Medical Complex Hospital, Quetta, were included. They were admitted in the ward and evaluated with history, physical examination and for staging investigations. Patients were then planned for chemotherapy comprising cyclophosphamide, doxorubicin, and vincristine with prednisolon (CHOP) and with rituximab (R-CHOP). After the first cycle of chemotherapy they were monitored for expected neutropenia in the ward. The neutrophil counts were repeated on days 7 and 10 following chemotherapy. Neutropenia was graded as defined in the operational definition and all the data were entered on a designed data sheet.Results: Forty two patients of NHL were included in this study, of which 34 patients received CHOP, and 08 patients R-CHOP, from march, 2010 to February, 2012. According to WHO classification, 24(57.1%) patients were of Diffuse large B-cell lymphoma (DLBCL), 08(19.0%) were follicular lymphoma (FL) and 04(9.5%) patients were Mantle cell lymphoma (MCL) and remaining 06(1430) are other types of NHL’s. 2(4.7%) of patients suffered from grage IV neutropenia (absolute neutrophil count of <0.5 x /L), 3(7.1%) had grade III Neutropenia (absolute. Neutrophil count of 0.5 x /L-0.9 x /L),3(7.1%) had Grade II neutropenia (absolute netrophil count 1.5 x /L-1.4 x /L) and 5(11.9%) had Grad I neutropenia (absolute netrophil count 1.5 x /L-1.9x/L). Other risk factors noted, i.e., cardiac, Liver and Renal comorbidities in 3(7.1%), 5(11.9%) and 4(9.5%) of patients respectively.Conclusion: Overall 30.8% of patients of NHL’s suffered from neutropenia of all grades post first cycle of chemotherapy comprising CHOP and R-CHOP.